The Effects of Brief Heat During Early Booting on Reproductive, Developmental, and Chlorophyll Physiological Performance in Common Wheat (Triticum aestivum L.) - Jiemeng Xu; Lowe, Claudia; Hernandez Leon, Sergio G.; Dreisigacker, Susanne; Reynolds, Matthew P.; Valenzuela Soto, Elisa M.; Paul, Matthew J.; Heuer, Sigrid (Frontiers Media, 2022)
Rising temperatures due to climate change threaten agricultural crop productivity. As a cool-season crop, wheat is heat-sensitive, but often exposed to high temperatures during the cultivation period. In the current study, a bread wheat panel of spring wheat genotypes, including putatively heat-tolerant Australian and CIMMYT genotypes, was exposed to a 5-day mild (34°C/28°C, day/night) or extreme (37°C/27°C) heat stress during the sensitive pollen developmental stage. Worsening effects on anther morphology were observed, as heat stress increased from mild to extreme. Even under mild heat, a significant decrease in pollen viability and number of grains per spike from primary spike was observed compared with the control (21°C/15°C), with Sunstar and two CIMMYT breeding lines performing well. A heat-specific positive correlation between the two traits indicates the important role of pollen fertility for grain setting. Interestingly, both mild and extreme heat induced development of new tillers after the heat stress, providing an alternative sink for accumulated photosynthates and significantly contributing to the final yield. Measurements of flag leaf maximum potential quantum efficiency of photosystem II (Fv/Fm) showed an initial inhibition after the heat treatment, followed by a full recovery within a few days. Despite this, model fitting using chlorophyll soil plant analysis development (SPAD) measurements showed an earlier onset or faster senescence rate under heat stress. The data presented here provide interesting entry points for further research into pollen fertility, tillering dynamics, and leaf senescence under heat. The identified heat-tolerant wheat genotypes can be used to dissect the underlying mechanisms and breed climate-resilient wheat.